Inggris - Subhan Maulidi Kun Bad'a Farohii; Fatchur Rohman; Sulisetijono Sulisetijono (Universitas Islam Negeri Mataram, 2023)
Research on the characterization of potential perennials to resist river erosion in the Brantas river border based on different environmental features in Malang, East Java has been carried out. The research aims to know the composition of plant species, plant diversity, and the dominance of perennials that can prevent erosion. The study used vegetation analysis with cruise methods, exploring perennials on the Brantas river border based on different environmental settings (residential industry, environment, fields). The results of the study found 49 species of plants in 25 families, the diversity of hard plants in the residential environment was high with H' 3.06 while in the industrial and rice fields/fields environment it was moderate with H' 2.67 (Industry) and H' 1.90 (fields). The dominant plants are Gigantochloa apus (Schult. f.) Kurz ex Munro (Industry) species, Calliandra houstoniana (Mill.) Standl. (Settlement) and Pinus merkusii Jungh. & Vriese ex Vriese. (fields) Many perennials in the study area can prevent erosion because these plants meet the criteria of a strong root system and economic value. Keywords: Perennials, Erosion, Border, Brantas River